2016
DOI: 10.1039/c6sc02103d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of P. aeruginosa c-di-GMP phosphodiesterase RocR and swarming motility by a benzoisothiazolinone derivative

Abstract: Pseudomonas aeruginosa swarming motility can be inhibited with a small molecule inhibitor of c-di-GMP phosphodiesterase, RocR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 70 publications
0
29
0
1
Order By: Relevance
“…reported a benzoisothiazolinone derivative ( 37 ) which was found by in silico screening against the structure of an E . coli PDE . This compound inhibited selectively c‐di‐GMP hydrolysis of the locally acting PDE RocR of P. aeruginosa with a K i of 83 μ m , but did not inhibit three other PDEs of P. aeruginosa whereby global cellular c‐di‐GMP levels remained unaffected (Figure ).…”
Section: Interference With Flagellar Motor Assembly and Functionmentioning
confidence: 99%
“…reported a benzoisothiazolinone derivative ( 37 ) which was found by in silico screening against the structure of an E . coli PDE . This compound inhibited selectively c‐di‐GMP hydrolysis of the locally acting PDE RocR of P. aeruginosa with a K i of 83 μ m , but did not inhibit three other PDEs of P. aeruginosa whereby global cellular c‐di‐GMP levels remained unaffected (Figure ).…”
Section: Interference With Flagellar Motor Assembly and Functionmentioning
confidence: 99%
“…Recently several reports have documented the roles of cyclic dinucleotide (c-di-GMP, c-di-AMP and cGAMP) phosphodiesterases in bacterial virulence 1 as well in innate immunity (cleavage of 2 0 3 0 -cGAMP) and probes, 55,56 such as the ones reported in this manuscript could be used to conrm the activity of expressed PDE enzymes or used to screen for inhibitors of dinucleotide phosphodiesterases. 19,57 …”
Section: Resultsmentioning
confidence: 99%
“…2), slightly decreased upon cleavage by RocR, 15 a c-di-GMP PDE that we have been interested in developing inhibitors against. 19 However, MANT-cdi-GMP has a bulky uorophore group appended to 2 0 -position of c-di-GMP and this steric block could account for the poor substrate prole for some PDEs. We recently reported that the replacement of one of the native nucleobases of c-di-GMP with 2-AP afforded a uorescent analog (compound 1, Fig.…”
Section: 42mentioning
confidence: 99%
See 2 more Smart Citations